Cycloachelous levigatus sp. nov., a new swimming crab (Crustacea: Decapoda: Portunidae) from the South China Sea - Koch, Milan (Zootaxa, 2021)
A new species of portunid crab from the genus Cycloachelous Ward, 1942 is described from Vietnamese waters. Cycloachelous levigatus sp. nov. is morphologically most similar to C. orbitosinus (Rathbun, 1911), which was originally described from the syntype series collected from Western Pacific area (Cargados Carajos Islands, Amirante Islands, Seychelles) and C. octodentatus (Gordon, 1938) described from one single male from Singapore. There are differences in the sternal segments, third maxilliped, chela, abdomen and male gonopode shapes. The specific status of C. levigatus sp. nov. is also clearly supported by molecular data. Aside from a comparison of this new species with other known congeners, new photographs of syntypes of C. orbitosinus and the holotype of C. octodentatus are also provided.